METODE BELAJAR DARING DENGAN MOTIVASI BELAJAR MAHASISWA TINGKAT I STIKES ST. ELISABETH MEDAN - Sr. Imelda Derang; Helinida Saragih; Jeka Ranita Br Sembiring Meliala (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
By defining initiation, direction, intensity, persistence, and quality of behavior in carrying out an action, motivation is defined as a strong inner and outer will. This has a significant impact on student learning motivation in relation to what is being learned, how to study, and when to choose to study online. The method employed is crucial to success in obtaining success in learning. Online learning is one of the electronic-based ways that can be carried out remotely and can make it easier for students to find various types of information needed to support their learning. The goal of the study was to ascertain how Level I STIKes St. Elisabeth Medan's learning motivation and online learning strategies relate to one another in 2020. This study used a descriptive analytic cross-sectional approach, total sampling, and 111 students as respondents. A Google form questionnaire was used to collect the data. Results: The level of online education Santa Elisabeth Medan students discovered 69 people (62 %) in the good category and 42 people (38%) in the moderate category. While 72 people (65 %) were in the high category of learning motivation, 29 people (26%) were in the medium category, and 10 people were in the low category (9%). Using Spearman's rho test for data analysis, it was possible to achieve a p value of 0.000 (p 0.05), indicating that there was a strong correlation between online learning strategies and students' motivation to study. Teachers are encouraged to provide more engaging instructional resources, such as animated videos, and to incorporate motivational movies into the teaching and learning process.